Translating Arabic Literary Metaphors: A Comparative Evaluation of ChatGPT-4.0 and Google Translate 2024 - Ohod Faisal Ahmed; Ida Kusuma Dewi; Mohammed Yunus Anis (Universitas Islam Negeri Palopo, 2025)
This research conducted a comparative evaluation of ChatGPT-4.0 and Google Translate 2024 in translating Arabic literary metaphors into English. We applied a qualitative research approach focusing on the novel